Mensuração das inovações : construção de um índice de ciência, tecnologia e inovação (ICT&I) para os estados brasileiros - Collet, Luana (2012)
This paper has had as a goal to review on a theoretical level how innovation takes place in order to better understand the ways in which innovation is measured and which are the variables involved in the process, from both Science, Technology and Innovation. After this review we tried to create a Science, Technology and Innovation Index for the Brazilian states, by means of a compilation of the indexes used in Brazil which can be measured with secondary data. The goal was to rank the states and compare the Science, Technology and Innovation Index with other indicators such as per capita GPD, HDI ann Gini. In order to do this we conceptually worked with what innovation is, the models for indicators, how innovation takes place in a systemic way, the importance of local productive clusters for the innovation process, as well as the new role of universities with entrepreneurial functions. In order to better propose the construction of a Science, Technology and Innovation Index, we first identified and organized the indicators that are used in Brazil. This paper deals with the difficulty in measuring innovation and proposes a ST&I index created from the data banks and information already available for the Brazilian states. The proposed index is divided into four categories: 1) Expenses Per Capita in S&T and R&D; 2) Scientific Research; 3) Qualified Education and Human Resources; Diffusion of Knowledge. The construction of each sub-index is described in details, as well as the classification per federation unit. The best classified states are the ones in the South and Southeast regions, and also the Federal District. The best classified state in the S&T Index was São Paulo, followed by Rio Grande do Sul, Distrito Federal, Rio de Janeiro and Paraná. The states that were placed last belong to the nort and northeast regions of Brazil. The state of Ceará is also noteworthy because, despite having achieved a fair position in the Science, Technology and Innovation Index, it has a very low per capita GDP and an average HDI.